Development, creation, and evaluation of puppetry program as an entertainment-education service of the city of Meycauayan Library - Sarza, Dominique Gabrielle R. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
In a generation where anything is accessible through the internet, information is everywhere. Relevant information are transferred through news and articles – there are very few television shows nowadays that contain relevant information such as values and history in the Philippines. These kinds of information are usually featured in documentaries, news programs and movies that are most of the time appealing to adults. However, in the information profession world, there are various ways to disseminate information, depending on the age of the target audience. Puppetry, a form of entertainment-education, is among the tools contributing to a child’s learning and development but is rarely conducted in libraries.